Dakwah Fardiyah Penyuluh Agama Islam Di Blok 51 Kelurahan Air Temam Kota Lubuklinggau - Sopiyan, Wawan (STAI Bumi Silampari, 2023)
Nowadays, with the development of information and communication technology, da'wah activities seem to be activities that are only related to lectures, cults, sermons which are watched either offline or watched on television, YouTube or other new media. The aim of this research is to find out how the fardiyah da'wah activities that were previously exemplified by Rosulullah SAW are also practiced by his people in this increasingly modern era. Researchers used descriptive qualitative methods in this research activity. In the research, it was found that the research object had been carrying out da'wah activities for a long time in an environment far from urban access. The research results show that fardiyah da'wah activities must be carried out with strong intentions, full of sincerity, patience and sufficient religious knowledge. So that fardiyah da'wah runs well and smoothly.